Kajian Pengaruh Ketebalan Kaca Evaporator Terhadap Energi Yang Diserap Kolektor Pada Proses Desalinasi Air Laut - Wawan Septiawan Damanik; Munawar Alfansury Siregar; Sudirman Lubis; Ahmad Marabdi Siregar (Fakultas Teknik UMSU, 2021)
The testing of desalination equipment is based on the increasing level of human need for the use of clean water. Improvement methods continue to be carried out with the aim of increasing the yield of clean water from desalination equipment. This research was conducted experimentally by providing a copper collector in a desalination device with a harpan to make it easier to absorb heat so that the water in the evaporator expands faster. By providing a variable difference in glass thickness, it is hoped that it can provide information that a good glass thickness can be applied to desalination equipment. The variation of the glass thickness is 4 mm and 5 mm with the same glass surface area. The results show that glass with a smaller thickness will make the desalination tool faster in absorbing heat energy. However, some conditions may also be considered to avoid damage to the glass. With the wind speed on the fourth day of testing which is 5.67 m/s and strong solar intensity reaching 397.14 W/m2, the energy absorbed by the collector reaches 3.72 kW/day on a glass thickness of 4 mm. Meanwhile, at a different thickness of 5 mm, the energy absorbed by the collector only reaches 2.72 kW/day. This shows that the difference in glass thickness plays a role in determining the occurrence of conduction heat transfer from outside the evaporator into the evaporator chamber.